Strategi Humas Polda Sulsel dalam Menjaga Citra Lembaga Kepolisian di Provinsi Sulawesi Selatan - Nugra Rianti Mallarangeng (Program of Communication Sciences, Faculty of Social and Political Sciences, UIM, 2020)
A good image of an institution will make it easier to achieve the goals set by both the individual and the organization. The large number of oblique reports about the police made the public think that the police's performance was questionable. This is what motivates the writer to find out the strategy of the Public Relations of the South Sulawesi Regional Police in maintaining the image of the Police institution which is the protector of the community, especially in South Sulawesi. Data collected by interview method. From the results of this study it can be concluded that the public relations communication strategy in building the image of the South Sulawesi Police has been carried out well, thanks to the roles between sub-sectors in the Public Relations Division of the South Sulawesi Regional Police so that a communication strategy is formed to carry out the task in this case building the image of the Polda Police. South Sulawesi, based on a communication strategy in the form of a Communicator (communicator), Relationship (Building), Back up Management (managing management), Good Image Maker (Creating Images). Factors that affect the public relations communication strategy in building the image of the South Sulawesi Police with the following supporting factors; There is an application of the role of each public relations subbid in the field of Public Relations in carrying out the main tasks and duties in building the image of the police itself, as well as the implementation of the functions, duties and powers of the Police according to the applicable SOTK Polda. While the inhibiting factors are as follows; There are police officers who neglect their duties, negative news about the Police, the speed of reporting in the media which emphasizes the Police's mistakes in carrying out their duties.